Fostering Academic Writers’ Plurilingual Voices - Broido, Monica; Rubin, Harriet (Journal of Academic Writing, 2020)
In today's global society, a majority of academic writers come from diverse linguistic backgrounds, where English is an additional language. Publishing in most academic journals, however, is governed by native-English norms. As instructors and tutors guiding novice plurilingual writers through these conventions so that their papers meet publishing standards, we feel that their voices and styles get lost in the process, and fear that the academic and scientific community may be losing out when these writers' work is not accepted. To understand how plurilingual novice writers experience writing for publication, we conducted in-depth interviews, followed by a content analysis of the interviews, which revealed recurring themes relating to barriers and gains from writing in English. We present these along with exemplary quotes from the respondents. Additionally, we examine the ways in which the publication world is changing and how these changes can aid novice writers, as well as consider ways in which academic writing boundaries can become more elastic and inclusive.